Uma revisão sistemática sobre o uso de agonistas e antagonistas do GnRH em pacientes más respondedoras à estimulação ovariana - Franco, J. G.; Baruffi, R. L R; Mauri, A. L. [UNESP]; Petersen, C. G. [UNESP]; Felipe, V.; Cornicelli, J.; Cavagna, M.; Oliveira, J. B A (My University, 2006)
The purpose of this investigation was to make a systematic review of the medical literature in order to compare the efficacy of GnRH antagonists and agonists for poor responders to ovarian stimulation. According to the data collected, the use of GnRH antagonist protocols showed better results in comparison to long protocols with a GnRH agonist regarding the following aspects: lower cycle cancellation rate due to poor ovarian response; higher number of oocytes retrieved; higher clinical pregnancy rate per initiated cycle. Nevertheless, these results were not observed when the flare-up protocols of GnRH agonists were used. Moreover the number of oocytes retrieved with GnRH agonist was significantly higher in relation to the GnRH antagonist.
A systematic review on the use of GnRH agonists and antagonists in patients with poor response to ovarian stimulation supression
Keywords: GnRH agonist; GnRH antagonist; Ovarian stimulation; Poor responders; buserelin; buserelin acetate; cetrorelix; ethinylestradiol plus levonorgestrel; ethinylestradiol plus norgestrel; ganirelix; gonadorelin agonist; gonadorelin antagonist; leuprorelin; recombinant follitropin; triptorelin; urofollitropin; clinical trial; controlled clinical trial; drug efficacy; human; low drug dose; medical literature; ovary cycle; ovary function; pregnancy rate; randomized controlled trial; review; systematic review